Dual BRAF/MEK blockade restores CNS responses in BRAF-mutant Erdheim–Chester disease patients following BRAF inhibitor monotherapy. Issue 1 (3rd March 2020) - Mazor, Roei D; Weissman, Ran; Luckman, Judith; Domachevsky, Liran; Diamond, Eli L; Abdel-Wahab, Omar; Shapira, Shirley; Hershkovitz-Rokah, Oshrat; Groshar, David; Shpilberg, Ofer
Abstract: Background: Erdheim–Chester disease (ECD), a rare inflammatory myeloid neoplasm, is known to be fundamentally reliant on the constitutive activation of the MAPK signaling pathway in the majority of patients. Consequently, inhibition of the V600E-mutant BRAF kinase has proven to be a safe and efficacious long-term therapeutic strategy for BRAF -mutant ECD patients. Nevertheless, in a subset of patients with CNS disease, the efficacy of long-term treatment may diminish, facilitating suboptimal responses or disease progression. Methods: We retrospectively describe 3 BRAF -mutant ECD patients whose treatment with Vemurafenib was upgraded to Vemurafenib/Cobimetinib due to either disease progression, insufficient response, or unacceptable toxicity. CNS response to therapy was evaluated using magnetic resonance imaging (MRI) and extra-cranial disease was monitored using 18 F-fludeoxyglucose positron emission tomography/computed tomography (PET/CT). Results: Three patients with a mean age of 52.6 years were treated with Vemurafenib for a mean duration of 26.6 months (range: 6–52). Monotherapies were upgraded to Vemurafenib/Cobimetinib dual therapy. The combination therapy was administered for a mean duration of 21 months (range: 19–23). All patients exhibited clinical and neurological improvement. Regression of lesions on MRI was noted in 2 patients. Both patients characterized by a PET-avid disease responded to the biological treatment regimen with complete metabolic remissions. Conclusion: Dual inhibition of BRAF and downstream MEK may be a safe and effective therapeutic strategy for BRAF -mutant ECD patients for whom BRAF inhibitor therapy proved insufficient and as such appropriate for the long-term management of CNS disease in ECD.